CLINICAL, BIOCHEMICAL AND FUNCTIONAL ASPECTS OF HARD DENTAL TISSUE ALTERATIONS IN PATIENTS WITH GASTROINTESTINAL DISEASES AND BILIARY DYSFUNCTION: A NARRATIVE REVIEW - Akhtamova Irodakhon Akbarovna; Rajabov Otabek Asrorovich (Modern American Journals, 2025)
Gastrointestinal diseases and biliary dysfunction are among the most prevalent chronic systemic disorders and are frequently associated with metabolic disturbances that affect multiple organs and tissues, including the oral cavity. In recent years, increasing scientific attention has been directed toward the relationship between gastrointestinal pathology and alterations in hard dental tissues, particularly enamel and dentin. These changes are primarily mediated by disturbances in mineral metabolism, acid–base balance, and salivary protective mechanisms.
Keywords: Hard dental tissues, enamel, dentin, gastrointestinal diseases, biliary dysfunction, saliva, demineralization, erosive tooth wear